INVESTORS REACT TO DISCLOSURE OF CARBON EMISSIONS AND ENVIRONMENTAL PERFORMANCE - Sanggi Asyari; Dianwicaksih Arieftiara (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
The current industrial development makes economic activities have to utilize natural resources which causes the conversion of forest functions and the use of fossil energy. So with industrial growth, carbon and greenhouse gas emissions tend to increase as well. The purpose of this study was to determine the effect of disclosure of carbon emissions and environmental performance on investor reactions. The population used is manufacturing companies in the food and beverage industry sub-sector as well as the cement sub-sector listed on the Indonesia Stock Exchange in 2018, 2019, and 2020. The number of samples in this study was 48, using purposive sampling method and secondary data, namely annual reports. The analytical method used is multiple linear regression analysis. The results of the study show that the disclosure of carbon emissions has no effect on investor reactions. Meanwhile, environmental performance affects the reaction of investors.